Energy from the Sea: Computational Modeling of an Overtopping Device - Iahnke, Silvana L P; Gomes, M N; Isoldi, Liercio A; Rocha, Luiz A O (2009 Third Southern Conference on Computational Modeling, 2009)
This work presents a brief study about the wave energy as well as a computational modeling of an overtopping device. The numerical simulation was performed with the FLUENT ® Computational Fluid Dynamic software code, employing the multiphase Volume of Fluid (VOF) model. The obtained results showed a satisfactory agreement between the numerical and analytical solutions, being the maximum difference calculated for the wave generation of approximated 4.6%. It was also observed that the knowledge of the wave height and an adequate ramp design are factors that determine the overtopping occurrence.